BOOK REVIEW THE FIFTH ELEMENT (Journal of the Spanish Institute for Strategic Studies, 2018)
The fifth element”, by Alejandro Suárez Sánchez-Ocaña is a tale ofespionage, war and terrorism from the perspective of new digitaltechnologies and their consequences. Written in a fast-paced but easygoingstyle, Suárez presents a succession of cyber-attacks, each one hot on the heels ofanother, to illustrate the risks and threats posed by cyberspace in 21st century society.On target in most of his evaluations and supporting data, Alejandro Suárez managesto raise the reader’s awareness of the vulnerability of the digital world and sensiblyincludes a section which also addresses its mitigating factors. Published in 2015, thebook chronicles attacks that have already become classics in a world in constantevolution and change. Although its conclusions remain valid, the eighteen monthsthat have gone by since the date of its first edition have meant that numerous and verysignificant events are not included.